Human development in the context of modern information society (Journal of Philosophy Culture and Political Science, 2023)
This article addresses the problem of human development in the modern information space. With the formation of the digital environment, the traditional way of life is changing. The main thesis of the analysis is that an individual plays an important role in the information society. The question of human development in the conditions of the information society, the transformation of education and science, stimulating the process of spiritual and moral education of the individual arises. To understand the role of man in the modern information society, we need first of all to identify and analyze the features of the information age.In this article, the authors examine the process of formation of the information society, as well as analyze the role of man as the main factor and resource for the development of the information society. In addition, on the basis of contemporary studies, the authors examine the features of science, education and human development in the context of the information society. New opportunities for human development in the information society and new challenges for science and education are discussed.Keywords: human development, information society, globalization, communication technology.